N-Palmitoylethanolamine Maintains Local Lipid Homeostasis to Relieve Sleep Deprivation–Induced Dry Eye Syndrome - Chen, Qi; Ji, Chunyan; Zheng, Ruihe; Yang, Longhe; Ren, Jie; Li, Yitian; Han, Yun; Zhou, Pan; Liu, Zuguo; Qiu, Yan (Frontiers in Pharmacology, 2020)
Sleep loss is considered to be one of the key factors associated with dry eye. A ‘stick over water’ mice model showed that sleep deprivation (SD) induced accumulation of lipids, hypertrophy and dysfunction of the lacrimal gland (LG), which decreased tears production, and caused dry eye symptoms. While, the specific pathophysiological mechanisms are still uncertain. In the present study, SD induced the decrease of endogenous lipid palmitoylethanolamide (PEA) in LG, which was mainly attributed to the high expression of the synthetic enzyme NAPE-PLD. Exogenous PEA treatment restored the local lipid metabolism homeostasis in LG to reduce lipids deposition, maintain endoplasmic reticulum and mitochondrial morphology, and improve acinar cell secretory function. PEA further prevented the corneal barrier function damage and improved dry eye symptoms caused by SD. The nuclear receptor PPAR-α was identified to mediate the above improvement of PEA. We describe here for the first time that PEA plays a role in SD-induced lacrimal gland pathogenesis and dry eye development. PEA and its metabolizing enzymes may serve as adjunctive therapeutic targets for treating the disease.